"I believe that it will be an amazing experience": pre-departure impressions of students on an Erasmus exchange programme. Issue 2 (3rd May 2016) - Jeanpierre, Eric; Broadbent, Graeme
Abstract : This article discusses responses to interviews forming the first part of a longitudinal study in which we seek to evaluate the short- and long-term impacts of the Erasmus experience on law students from a British university of the effects of a year spent abroad at a partner institution. Law is a particularly fruitful subject area for such a study, as students will be studying in a country with a different legal culture to that with which students are familiar. It is clear though that the experience is not limited to legal study but extends to working within a different educational culture, as well as living in another country over an extended period of time. The object of this paper is to explore and analyse actual expectations and experiences of students more fully so as to understand the impact of the Erasmus programme on their lives and careers. Whilst the data collected to date, mainly through in-depth semi-structured interviews, covers a limited population, the study identifies a wide-ranging set of motivational factors, though the mixture of, and weight given to, academic and personal motivations that vary from student to student.